Způsoby řízení developerských projektů - Samek, David (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Teoretická část této diplomové práce je zaměřena na vysvětlení souvisejících pojmů z oblasti developerské činnosti. V praktické části potom analyzuje developerskou činnost společnosti Lettenmayer & Partner

The theoretical part of this master’s thesis is focused on explaining the related concepts of the development activities. In the practical section analyzes the development activities of Lettenmayer & Partner Company.
Ways of Developer Project Management
Keywords: Developerský projekt developerská činnost developer nemovitost řízení projektu; Development project developer property real estate developer activities project management